Motivasi Mahasiswa Tahfidz dalam Mengikuti Sima’an Al-Qur’an di IAIN Ponorogo - Afif Syaiful Mahmudin (UIN Mataram, 2021)
Sima'an Al-Qur'an is mutual listening and listening to the readings between two or more people, if one person reads then the other listens. This activity is very useful for one's memorization, before attending sima'an, one will prepare juz-juz to be read by adding hours for muraja'ah. Like the Sima'an Al-Qur'an activity which is held at the Ulin-Nuha Mosque every Kliwon Friday by IAIN Ponorogo students. The formulation of the research problem is, how are the students' intrinsic motivation and extrinsic motivation in participating in Sima'an Al-Qur'an activities at the Ulin-Nuha Mosque, State Islamic Institute (IAIN) Ponorogo? To answer this question, the researcher uses a qualitative approach (case study), using analytical methods through reduction, display and conclusion. The data collection techniques used were observation, interviews and documentation, while the researcher was the key instrument. From the results of this study it was found that: (a) Intrinsic motivation of students to follow Sima'an Al-Qur'an every Kliwon Friday at the Ulin-Nuha mosque IAIN Ponorogo because it is to improve academic achievement related to Al-based courses al-Quran and the quality of memorization that is their duty as a memorizer of the Koran. (b) Extrinsic motivation is the encouragement from family and colleagues related to the ability to maintain memorization, the process of academic competition and the existence of learning scholarships.